Presence of neutralizing SARS‐CoV‐2 antibodies in asymptomatic population of N'Djamena, Chad - Andrillene Laure Deutou Wondeu; Mahamat Fayiz Abakar; Federica Frasca; Aleyo Zita Nodjikouambaye; Fatima Abdelrazakh; Nathan Naibei; Guy Rodrigue Takoudjou Dzomo; Djallaye Djimtoibaye; Joseph Mad‐Toingue; Carolina Scagnolari; Guido Antonelli; Giulia Linardos; et al. (Immunity, Inflammation and Disease, 2024)
Abstract Introduction Neutralizing antibodies (NAbs) are an important specific defence against viral infections, as these antibodies bind to specific receptor(s) and block the viral entry. NAbs assessments are therefore useful in determining individual or herd immunity to SARS‐CoV‐2. This study aims to deepen the investigation by assessing the positivity rate of neutralizing anti‐spike antibodies to understand the real protection of the studied population against SARS‐CoV‐2. Methods This study involved 260 plasma samples from a larger cohort of 2,700 asymptomatic volunteer donors, enrolled between August and October 2021 in health facilities of N'Djamena. In this study four different kits and techniques including the pseudotype assay have been used and compared with detect the SARS‐CoV‐2 antibodies. Pseudotyped vesicular stomatitis virus (VSV), was used both the identify and measure the NAbs that to evaluate the performance of two cheaper and easy to use commercial kits, specific for the detection of receptor‐binding domain antibodies (anti‐RBD) against the SARS‐CoV‐2 spike protein. Results The VSV spike neutralization assay showed that 59.0% (n = 59) samples were positive for NAbs with titers ranging from 1:10 to 1:4800. While 23 out the 41 negative NAbs samples were detected positive using anti‐RBD (Abbott) test. Furthermore, a direct and significant strong correlation was found between NAbs and anti‐RBD, specifically with Abbott kit. Taken together, the Roche and Abbott methods indicated agreement at the high concentrations of antibodies with the VSV‐pseudovirus method. Abbott and Roche indicated a good sensitivity, but the Abbott system test appeared to have better specificity than the Roche test. Conclusion Our findings indicated a high presence of NAbs against SARS‐CoV‐2 spike protein among asymptomatic individuals in N'Djamena. This could be one of the reasons for the low severity of Covid‐19 observed in this area, given the key role of NAbs in blocking SARS‐CoV‐2 infection.